Scheduling elective patients based on sequence-dependent setup times in an open-heart surgical department using an optimization and simulation approach. (December 2019) - Hamid, Mahdi; Hamid, Mojtaba; Musavi, MirMohammad; Azadeh, Ali
The surgery ward is the most expensive and profitable section of a hospital. The decisions made in this section therefore produce significant effects on the overall performance of the hospital. Planning and scheduling of the surgeries in the operating rooms would obviously lead to the enhancement of the performance of the operating rooms. The setup time of the operating rooms is a very important factor in initiating next surgeries and consequently in the scheduling of elective patients. The preparation time is usually affected by the sequence of the surgeries, especially in critical and longer surgeries, such as open-heart surgeries. In this study, a two-stage procedure is applied to improve the performance of the open-heart surgical department. In the first stage, a mathematical model is proposed for planning and scheduling of the surgeries in the open-heart surgery ward, considering the sequence-dependent setup times. In the next stage, an estimation of the optimum number of intensive care unit beds is provided using the discrete event simulation method. Finally, using a real-life example, the applicability of the proposed model is demonstrated and an analysis of the effect of the recommended number of intensive care unit beds—extracted from the simulation model—on the performance of the surgical theater is performed.